IMPLEMENTASI PENGGUNAAN PODCAST SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK PADA SISWA KELAS V UPTD SDN 117 INPRES KURUSUMANGE KABUPATEN MAROS - Muhammad Akhir; Abdan Syukur; Nabila Ayu Febrianti (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
The main problem in this study is how the use of podcasts as a learning medium for class Va in improving students' listening skills, according to students' learning needs and how the impact of using podcasts on the listening skills of class Va students at UPTD SDN 117 Inpres Kurusumange. This study aims to determine the use of podcasts as a learning medium can improve listening skills according to students' learning needs and can determine the impact of applying podcasts on the listening skills of class Va students at UPTD SDN 117 Inpres Kurusumange. This type of research is research that uses a qualitative descriptive research method intended to be able to describe and illustrate clearly and in detail the implementation of the use of podcasts as a learning medium to improve listening skills in students. Data were collected through observation, interviews with teachers and students, and questionnaires. The results showed that the initial use of podcasts implemented by teachers and schools at the UPTD SDN 117 Inpres Kurusumange, Maros Regency, especially in grade 6, was still ineffective for student learning, particularly in listening skills. This was due to several factors, including the ineffective use of podcast media, the choice of content that was less interesting for students, inadequate applications, and the selection of long-duration content. After using the updated podcast, it has successfully shown positive results using a relatively popular application with interesting and comprehensive features, content that is not long and interesting for students, which can prevent students from getting bored while listening, thus improving the listening skills of grade 6 students. Keywords: Use of podcasts, improving listening skills, impact of podcast use on students' listening skills